Cocrystals of 1, 4‐diethynylbenzene with 1, 3‐diacetylbenzene and benzene‐1, 4‐dicarbaldehyde exhibiting strong nonconventional alkyne–carbonyl C—H…O hydrogen bonds between the components. Issue 10 (26th September 2016) - Bosch, Eric
Abstract : The 1:1 cocrystal of 1, 4‐diethynylbenzene with 1, 3‐diacetylbenzene and the 1:1 cocrystal of 1, 4‐diethynylbenzene with benzene‐1, 4‐dicarbaldehyde feature a strong nonconventional ethynyl–carbonyl sp ‐C—H…O hydrogen bond between the components. Abstract : Weak interactions between organic molecules are important in solid‐state structures where the sum of the weaker interactions support the overall three‐dimensional crystal structure. The sp ‐C—H…N hydrogen‐bonding interaction is strong enough to promote the deliberate cocrystallization of a series of diynes with a series of dipyridines. It is also possible that a similar series of cocrystals could be formed between molecules containing a terminal alkyne and molecules which contain carbonyl O atoms as the potential hydrogen‐bond acceptor. I now report the crystal structure of two cocrystals that support this hypothesis. The 1:1 cocrystal of 1, 4‐diethynylbenzene with 1, 3‐diacetylbenzene, C10 H6 ·C10 H10 O2, (1), and the 1:1 cocrystal of 1, 4‐diethynylbenzene with benzene‐1, 4‐dicarbaldehyde, C10 H6 ·C8 H6 O2, (2), are presented. In both cocrystals, a strong nonconventional ethynyl–carbonyl sp ‐C—H…O hydrogen bond is observed between the components. In cocrystal (1), the C—H…O hydrogen‐bond angle is 171.8 (16)° and the H…O and C…O hydrogen‐bond distances are 2.200 (19) and 3.139 (2) Å, respectively. In cocrystal (2), the C—H…O hydrogen‐bond angle is 172.5 (16)° and the H…O and C…O hydrogen‐bond distances are 2.25 (2) and 3.203 (2) Å, respectively.